Ticagrelor Protects the Heart Against Reperfusion Injury and Improves Remodeling After Myocardial Infarction. Issue 8 (August 2015) - Ye, Yumei; Birnbaum, Gilad D.; Perez-Polo, Jose R.; Nanhwan, Manjyot K.; Nylander, Sven; Birnbaum, Yochai
Abstract : Objective—: In addition to P2Y12 receptor antagonism, ticagrelor inhibits adenosine cell uptake. Prior data show that 7-day pretreatment with ticagrelor limits infarct size. We explored the acute effects of ticagrelor and clopidogrel on infarct size and potential long-term effects on heart function. Approach and Results—: Rats underwent 30-minute ischemia per 24-hour reperfusion. (1) Ticagrelor (10 or 30 mg/kg) or clopidogrel (12.5 mg/kg) was given via intraperitoneal injection 5 minutes before reperfusion. (2) Rats received ticagrelor acute (intraperitoneal; 30 mg/kg), chronic (oral; 300 mg/kg per day) for 4 weeks starting 1 day after reperfusion or the combination (acute+chronic). Another group received clopidogrel (intraperitoneal [12.5 mg/kg]+oral [62.5 mg/kg per day]) for 4 weeks. (1) Ticagrelor dose-dependently reduced infarct size, 10 mg/kg (31.5%±1.8%; P <0.001) and 30 mg/kg (21.4%±2.6%; P <0.001) versus control (45.3±1.7%), whereas clopidogrel had no effect (42.4%±2.6%). Ticagrelor, but not clopidogrel, increased myocardial adenosine levels, increased phosphorylation of Akt, endothelial NO synthase, and extracellular-signal-regulated kinase 1/2 4 hours after reperfusion and decreased apoptosis. (2) After 4 weeks, left ventricular ejection fraction was reduced in the vehicle-treated group (44.8%±3.5%) versus sham (77.6%±0.9%). All ticagrelor treatments improved left ventricular ejection fraction, acute (69.5%±1.6%), chronic (69.2%±1.0%), and acute+chronic (76.3%±1.2%), whereas clopidogrel had no effect (37.4%±3.7%). Ticagrelor, but not clopidogrel, attenuated fibrosis and decreased collagen-III mRNA levels 4 weeks after ischemia/reperfusion. Ticagrelor, but not clopidogrel, attenuated the increase in proinflammatory tumor necrosis factor-α, interleukin-1β, and interleukin-18, and increased anti-inflammatory 15-epi-lipoxin-A4 levels. Conclusions—: Ticagrelor, but not clopidogrel, administered just before reperfusion protects against reperfusion injury. This acute treatment or chronic ticagrelor for 4 weeks or their combination improved heart function, whereas clopidogrel, despite achieving a similar degree of platelet inhibition, had no effect. Abstract : Supplemental Digital Content is available in the text.